Pulmonary Hydatid Disease with Aspergillosis - An Unusual Association in an Immunocompetent Host - Rahul Chanderhas GOYAL; Ruchita TYAGI; Bhavna GARG; Atul MISHRA; Neena SOOD (Federation of Turkish Pathology Societies, 2019)
Echinococcosis is a common cause of pulmonary cavities. Aspergillus fumigatus, a saprophytic fungus, can colonise pulmonary cavities caused by tuberculosis, sarcoidosis, echinococcosis, bronchiectasis and neoplasms. Infection by Aspergillus is often seen in immunosuppressed cases. However, co-infection of Aspergillus with pulmonary echinococcosis is unexpected and very unusual, especially in an immunocompetent patient. We present the case of a 45-year-old immunocompetent male who came with non-resolving pneumonia and fever for 8 months and dyspnoea since 15 days accompanied by recurrent episodes of hemoptysis since 5 days. Chest X Ray and Computed Tomography scan showed a cystic lesion in the middle lobe of the right lung. Middle lobectomy with video-assisted thoracoscopic surgery was performed and histopathology revealed ectocyst of Hydatid cyst which was also colonised by septate fungal hyphae exhibiting acute angled branching, morphologically consistent with Aspergillus. Gomori Methanamine Silver and Periodic Acid Schiff stains highlighted the hyphae of Aspergillus as well as the lamellated membranes of ectocyst and an occasional scolex of Echinococcus. Sections from surrounding lung parenchyma also showed these fungal hyphae within an occasional dilated bronchus. Thus a diagnosis of dual infection of Aspergillosis and Pulmonary Echinococcosis was established. The possibility of dual infection by a saprophytic fungus must be kept in mind while dealing with a case of a cavitary lesion in long-standing and non-resolving pneumonia, even in an immunocompetent patient. Establishing the correct diagnosis of Aspergillosis with Echinococcosis is essential for proper and complete management.